First, we substitute y = 3x - 4 into the first equation:
-4x + 4(3x - 4) = -40
-4x + 12x - 16 = -40
8x - 16 = -40
8x = -24
x = -24/8
x = -3
Now that we have found the value of x, we substitute it back into the second equation to find the value of y:
y = 3(-3) - 4
y = -9 - 4
y = -13
Therefore, the solution to the system of equations is (-3, -13).
Solve the system of equations by substitution.
−4x+4y=−40
y=3x−4
This question requires you to show your work.
(1 point)
Responses
(6, 4)
(6, 4)
(3, 7)
(3, 7)
(1,−1)
open paren 1 comma negative 1 close paren
(−3,−13)
open paren negative 3 comma negative 13 close paren
1 answer